Etika Pedagang menurut Al-Qur’an dan Sunnah - Nahlah - Nahlah (ITB AAS INDONESIA Surakarta, 2023)
The profession of a trader is a profession that is in great demand by many people. And like other professions, this profession is inseparable from procedures and rules based on government laws and sharia based on the Al-Quran and Hadith. This profession is also very noble from an Islamic point of view, including the eight groups promised by Allah SWT to get the Throne on the Day of Judgment. Besides that, there are many other advantages. Of course, it is accompanied by several conditions that must be met to get this priority, among other things, honesty, straightforward selling, and others. This study aims to describe ethics in trading as reported in the Al-Quran and Hadith, then synchronized with business ethics according to modern economics. The research uses SLR (Systematic Literature Review) with data sources from the Al Quran, Hadith, and several journals. The study results show that the rules or ethics of doing business in a modern economy are also contained in the rules or ethics of trading according to the Al Quran and Hadith. Even more complex than what is in the Al-Quran and Hadith.